2014
DOI: 10.1139/cjp-2013-0522
|View full text |Cite|
|
Sign up to set email alerts
|

Thickness dependence of electron transport in pure a-Se photoconductive films

Abstract: Electron transport in vacuum-deposited a-Se films with thicknesses varying from 13 to 501 m has been investigated by conventional time-of-flight (TOF) and interrupted field TOF experiments. To separate the influences of electric field and the thickness, all TOF experiments were performed at a constant electric field. It has been found that the electron mobility is relatively constant in thick films (L > 50 m) and increases in thinner films (L < 50 m) with decreasing thickness. On the other hand, the electron l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…11. For a-Se films of 100 m, as in the present case, we can assume that both e and e are reasonably thickness independent, and represent meaningful charge transport parameters.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…11. For a-Se films of 100 m, as in the present case, we can assume that both e and e are reasonably thickness independent, and represent meaningful charge transport parameters.…”
Section: Resultsmentioning
confidence: 98%
“…The hole transport in a-Se and stabilized a-Se is well known to be nondispersive [9,10] and the measured transport parameters do not depend on the film thickness. In the case of electron transport, the drift mobility, e , and the lifetime, e , are both relatively thickness independent for such thick films as shown in a paper in this issue [11].…”
Section: Methodsmentioning
confidence: 91%
“…The latter becomes particularly striking when measured in samples with varying thicknesses at a constant electric field. In our previous paper [88] we investigated the dispersive transport of electrons in a-Se and showed how the electron mobility depends on sample thickness. The dependence became insignificant in thick samples ([100 lm).…”
Section: Dispersive Versus Non-dispersive Transportmentioning
confidence: 99%
“…The experimental TOF data used in this work have been extracted primarily from two main sources: (a) works carried out by the authors and reported previously in [41][42][43] and (b) TOF measurements carried out at Xerox by Pfister and Scher and reported in [44]. The two sets of samples are labelled S and X respectively.…”
Section: Introduction and Perspectivesmentioning
confidence: 99%
“…18,19 For photoconductive layers that are thicker than 50 lm, one can also simply use l e and s e to describe the electron transport. 20 These charge transport parameters in the product form l e s e and l h s h , called electron and hole ranges, control the collection efficiency of x-ray generated charges inside the photoconductor. 21,22 The charge collection efficiency, of course, is one the factors that control the x-ray sensitivity; but, nonetheless, an important factor.…”
Section: Introduction and Objectivesmentioning
confidence: 99%